1981
DOI: 10.7326/0003-4819-95-3-360
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography in Patients with Psychiatric Illnesses: Advantage of a "Rule-In" Approach

Abstract: Computed tomography (CT) is used commonly to "rule-out" disease. In 123 consecutive patients with psychiatric diseases in three institutions, 105 CT scans (85.4%) interpreted as normal or normal except for atrophy did not influence management, only reassured clinicians and patients. Incidental and false positive findings were more numerous than true positive findings. All six true positive findings occurred in patients with focal findings on neurologic examination; four led to management changes. The lower 954… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
2

Year Published

1985
1985
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 11 publications
2
40
2
Order By: Relevance
“…No previous study has reported such a high percentage of abnormal brain scans as found in our study, which could be due to the inclusion of a higher percentage of elderly patients (average age 70 years) compared with earlier studies, 3,5 as with advanced age, more CT brain abnormalities can be expected. The majority of patients in our study had dementia, which is a common condition in the elderly population.…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…No previous study has reported such a high percentage of abnormal brain scans as found in our study, which could be due to the inclusion of a higher percentage of elderly patients (average age 70 years) compared with earlier studies, 3,5 as with advanced age, more CT brain abnormalities can be expected. The majority of patients in our study had dementia, which is a common condition in the elderly population.…”
Section: Discussioncontrasting
confidence: 45%
“…In the literature, a study reported that abnormal scans correlated with focal findings on neurological examination. 3 Another study showed that when a history of neurological disorder or neurological/organic mental signs was absent then brain scans were normal in 75 per cent of cases but when both were positive scans were abnormal in 74 per cent of cases and when both history/examination and electroencephalography (EEG) was abnormal the scan were abnormal in 92 per cent of cases. 5 In our study not all patients had had an EEG, hence we could not compare these results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations